A First Glimpse into the Ultimate Absolute. The Emergence of Genetic Analyses in Husserl’s Beranuer Manuscripts on Time-Consciousness and the Exploration of the Realm of Passivity - Giubilato, Giovanni Jan (Philosophy Kitchen - Rivista di filosofia contemporanea, 2020)
Starting by pointing out the deep interconnections between temporality and passivity within phenomenology, the present paper intends to contribute with a reconstruction of Husserl’s “first glimpses” into the sphere of passivity and its genesis based on the Beranuer Manuscripts on Time-Consciousness (1917-18). To do so, it will follow a disposition in four stages: after a brief introduction, section I will display the emergence of the genetic methodology and its functional position within the broader context of the architectonic system of phenomenology. After that, section II will follow the development of the notion of “absolute consciousness” by clarifying the constitutive problematic of time-consciousness and the related problem of an infinite regress (that threatened Husserl’s thought for many years). Section III will expose the first genetic model of time-consciousness as developed in the Bernauer paying particular attention to the discover of a transcendental realm of passivity and preegoic constitution. Finally, section IV will provide a translation of Eugen Fink’s disposition draft for the edition of Husserl’s Bernauer Manuscripts, as he and Husserl planned it around 1930. Those documents can provide a deep understanding of Husserl’s texts, of the problems related to consciousness self-constitution and its relation with the questions concerning a phenomenology of passivity and passive synthesis.